CRIME – BETWEEN CONCEPT AND DEFINITION IN THE EUROPEAN UNION - SIMONCA, Marcel (International Journal of Legal and Social Order, 2022)
The present paper presents itself as a comparison between criminal legislation that exist within the EU territory, as well as a theoretical analysis of some criminal law institutions which entails reverberations in the criminal procedural law as well. But these follow-ups go beyond these aspects. The theoretical steps that were assumed by this paper also knows profound practical implications, thus going beyond the abstract realm of theory and into practice, proving once again how important it is to posses the neccesary knowledge when it comes to compared law and not only that, but also the importance of that knowledge. The legislator cannot and should not remain indifferent regarding the signaled situations alongside this paper thus imposing the need to straighten, where neccesary, the impossible or contradictory situations.